The Effectiveness of Arbitration as A Commercial Dispute Resolution Solution in Indonesia - Sujati, Ananda; Yusufa, Joni; Hermawan, Dede; Safitri, Pradita Wuri; Anggraeni, Happy Yulia; Sagita, Praniko Imam (CV. Publikasi Indonesia, 2025)
Despite being regulated in Law Number 30 Year 1999, the effectiveness of arbitration in Indonesia still faces various challenges, such as lack of public understanding, high costs for small businesses, and limited arbitration infrastructure in the regions. Therefore, there is a need to evaluate and strengthen the role of arbitration to ensure that this mechanism can be a quick, fair solution and support business sustainability in Indonesia. The purpose of this study is to assess the extent to which arbitration has been able to be an effective solution in resolving commercial disputes in Indonesia, identify factors that influence its success, and provide recommendations to increase its efficiency and trustworthiness as a fair and speedy dispute resolution alternative. This research uses a descriptive method with a qualitative approach to describe phenomena systematically and accurately. Data was collected through documentation techniques, analyzing various relevant documents such as reports, archives, or articles. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing validated through triangulation. The results showed that arbitration is an effective commercial dispute resolution mechanism in Indonesia because it offers a fast process, affordable costs, and a final and binding award. Its advantages include flexibility, confidentiality, and international recognition through the New York Convention. However, its optimization requires strengthening regulations and education to overcome challenges such as the lack of understanding of business actors and inconsistencies in the application of the law.